Energy investments : an adaptive approach to profiting from uncertainties - Barcelona, Ricardo G. (Palgrave Macmillan, 2017)
'Ricardo Barcelona addresses the thornier issues of energy strategy. In this book he moves from the certainties assured by financial modelling to explore the tough questions that astute practitioners ask themselves - why do things never turn out as they were projected? Is energy strategy always going to be a tale of unfulfilled promises? His research findings and his insights make a must read for anyone in this field.' --Patrick H. "Paddy" Miller, Author, Innovation as Usual, Hong Kong The book offers rigour, depth, and relevance in tackling approaches that prove sustainable and transformational for business and society.' --Juan Miranda, Managing General Director, Asian Development Bank 'The book is timely in that it provides good insights on how to address the uncertainty and volatility facing today's energy markets. A good read for anyone involved in the energy sector.' --Stephen A. Paradies, Board Director, Union Bank, and former Chief Financial Officer, Aboitiz Equity Ventures, Philippines 'Containing original insights into the financing and economics of the energy industry, this book should be read by those working in and studying the future of the energy sector.' --David Parker, Emeritus Professor of Economics, Cranfield University School of Management, and former member, Competition Commission, United Kingdom This book examines what lies behind the uncertainties surrounding the fuel and power markets. Exploring the role of renewables and how they potentially disrupt or create opportunities, it challenges widely accepted wisdoms in investment. The author asks questions such as: Are "business as usual" strategies that favour fossil fuels the best route to future prosperity? What prospects do firms face when their competitors diversify into renewables? Why do generous subsidies to renewables often fail to achieve wide-scale deployment? Illustrating how real options and option games reasoning yield vastly different insights from those gained from NPVs, Energy Investments offers case studies and simulations to demonstrate how firms can benefit from the methods it showcases.
Keywords: Uncertainty.; Renewable energy sources -- Management.; Industrial management -- Environmental aspects.; Clean energy industries.; elektronické knihy; electronic books